Public or Private? An Attempt to Interpret the Social-Economic Purpose and Differences between Wells Located on a Przeworsk Culture Settlement (Based Interdisciplinary Research – Example of the Site in Kwiatków) - Piotrowska, Magdalena (Acta Archaeologica Lodziensia, 2019)
The aim of this article is to present the results of the archaeological analysis carried out on two wells from the site Kwiatków 11/20 (Brudzew commune, Greater-Poland Voivodeship) against a background of the geochemical and lithological data, as well as to outline the lithological and geological conditions of the surroundings of the excavated area. Within this settlement more than 100 wells were recorded. Most of the wells discovered have features of the Przeworsk culture from the first centuries AD. The analysis and interpretation of the data obtained (thanks to interdisciplinary research) helps us to understand the validity of use and functions of the wells within the site mentioned, and their social aspects. Thanks to the cooperation of specialists representing various scientific fields, it was possible to identify some differences not only in the chronology of both fields analyzed, but also in their function within the area of the settlement.